Ichnology and sedimentology of large tetrapod burrows in the latest Early Triassic Katberg Formation, south-eastern main Karoo Basin, South Africa - Krummeck, William Desmond (Department of Geological Sciences, 2015)
Trace fossils in the form of large (~11 cm diameter and up to 2 m in length) burrows were studied at three localities in the Early Triassic Katberg Formation in the south-eastern and central parts of the main Karoo Basin, Eastern Cape, South Africa. The most interesting site, Hobbs Hill, northwest of Cathcart (Eastern Cape) has numerous burrows, contains an exceptionally well exposed sedimentary succession and bone beds. This site is also the type locality for the holotype of the parareptile Kitchingnathus untabeni (BP/1/1187). The aims of this dissertation are to: 1) reconstruct the local paleoenvironments of the burrow localities; 2) determine the purpose of the burrows; 3) identify the possible burrow makers based on the sedimentology and burrow morphology and 4) attempt to use photogrammetry and low-cost hardware to produce 3D digital burrows for improved descriptions. Insights into the survival strategies and behaviours of organisms during the P/T extinction recovery period are explored. Detailed analysis is mainly done on observations from the Hobbs Hill site; the results and interpretations are important for and compatible with the entire Katberg Formation. The interactions between the physical (sedimentary) and biological (animal behaviour) processes are important in ichnology and paleoenvironmental reconstruction. The analyses have therefore been undertaken through a multidisciplinary approach based on ichnological, sedimentological, petrographical, stratigraphic and paleontological evidence, gathered both in the field and laboratory.